The Difference between Problem Based Learning Model and Discovery Learning Model on Students' Critical Thinking Ability - Arifianto, Andrian; Koeswanti, Henny Dewi (Journal for Lesson and Learning Studies, 2022)
The success of teachers in carrying out the learning process is influenced by several factors, one of which is the accuracy in the selection of learning models. This study aims to analyze the differences between the PBL model and the discovery learning model in improving students' critical thinking skills. The sample of this research is 27 students. This research is an experimental study using a non-equivalent control group design. The instrument used to measure critical thinking skills is a questionnaire. Prerequisite test using normality test and homogeneity test. Data analysis used t-test (t-test for independent samples). The results showed that there were significant differences in students' critical thinking skills using the PBL model and the discovery learning model in fourth grade students. The difference in the average score of critical thinking skills in the PBL model gets an average score of 68.44, and the discovery learning model gets an average score of 57.09. Therefore, the PBL model can be interpreted as superior to the discovery learning model in terms of critical thinking skills. This is supported by the results of the t-test which has a sig (two-sided) value of 0.000 < 0.05, Ho is rejected and Ha is accepted. This means that the critical thinking ability of the PBL model is significantly more effective than the discovery learning model.